Weaving Indigenous and Western knowledge systems across a continuum of knowledge and decision-making spaces - Natalie C Ban; Hannah V Watkins; Robyn E Forrest; Alejandro Frid; Carrie A Holt; Sierra J Hall; Christina N Service; Luisa Ramirez; Daniel L Curtis; Kyle L Wilson; Lawrence Ignace; Andrea J Reid; et al. (Current Opinion in Environmental Sustainability, 2026)

Restoring the wild east: Predicting public support for cougar and red wolf reintroduction in the eastern United States - Benjamin Ghasemi; Jeremy T. Bruskotter; John A. Vucetich; L. Mark Elbroch; Robyn S. Wilson; Neil H. Carter; Axel Moehrenschlager; Shelby Perry; Joseph W. Hinton (Biological Conservation, 2026)

Environmental drivers of tropospheric bromine and mercury variability in coastal East Antarctica - Neil C. Page; Jenny A. Fisher; Stephen R. Wilson; Robyn Schofield; Robert G. Ryan; Sean Gribben; Andrew R. Klekociuk; Grant C. Edwards; Anthony Morrison (Atmospheric Environment, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Social targeting conservation subsidies in the Western Lake Erie Basin - Matthew Ashenfarb; Carrie Dale Shaffer-Morrison; Robyn Wilson; Sandra Marquart-Pyatt; Rebecca Epanchin-Niell (Journal of Environmental Management, 2024)

Climate change impacts on crop yields: A review of empirical findings, statistical crop models, and machine learning methods - Tongxi Hu; Xuesong Zhang; Sami Khanal; Robyn Wilson; Guoyong Leng; Elizabeth M. Toman; Xuhui Wang; Yang Li; Kaiguang Zhao (Environmental Modelling & Software, 2024)

Assessing potential of the Geostationary Littoral Imaging and Monitoring Radiometer (GLIMR) for water quality monitoring across the coastal United States - Blake A. Schaeffer; Peter Whitman; Ryan Vandermeulen; Chuanmin Hu; Antonio Mannino; Joseph Salisbury; Boryana Efremova; Robyn Conmy; Megan Coffer; Wilson Salls; Hannah Ferriby; Natalie Reynolds (Marine Pollution Bulletin, 2023)

Re‐imagining the precautionary approach to make collaborative fisheries management inclusive of Indigenous Knowledge Systems - Alejandro Frid; Kyle L. Wilson; Jennifer Walkus; Robyn E. Forrest; Mike Reid (Fish and Fisheries, 2023)
Fisheries science uses quantitative methods to inform management decisions that reflect cultural preferences which, in turn, indirectly influence the states of ecosystems. To date, it has largely supported Eurocentric preferences for the commodification of marine organisms under the tenets of maximum sustainable yield, whereby abundances are intentionally maintained far below their historical baselines despite broader socio‐ecological trade‐offs. In contrast, Indigenous Knowledge Systems (IKS) adhere to the principle of “take only what you need and leave lots for the ecosystem,” implementing lower fishery removals to support socio‐ecological resilience. Despite the power imbalance favouring Eurocentric preferences in decision‐making, fisheries scientists increasingly recognize that the pairing of IKS and Western science, or Two‐Eyed Seeing, would lead to more holistic management goals. For recognition to transcend tokenism, meaningful collaborations and co‐governance structures underlying knowledge co‐production must carry through to legislated policy changes. Using recent co‐governance developments for fisheries management and spatial protections involving federal, provincial and Indigenous governments in Pacific Canada, we illustrate how the precautionary approach, including reference points and harvest control rules broadly applied in international fisheries, could be revised to make collaborative fisheries management compatible with IKS and improve biodiversity and fisheries protections. Our recommendations may create socio‐economic trade‐offs at different timescales for commercial fishers. Pre‐empting that challenge, we discuss IKS‐compatible economic approaches for addressing shorter term costs arising from reduced exploitation rates. Although our case study derives from Pacific Canada, the insights provided here are broadly applicable elsewhere in the world.

Biomonitoring of heavy metals in the feathers of House crow (Corvus splendens) from some metropolitans of Asia and Africa - Farheena Iqbal; Robyn Wilson; Qasim Ayub; Beng Kah Song; Urszula Krzeminska-Ahmedzai; Amin Talei; Andreas Aditya Hermawan; Sadequr Rahman (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The genetic drivers for the successful invasive potential of a generalist bird, the House crow - Farheena Iqbal; Urszula Krzeminska-Ahmadzai; Qasim Ayub; Robyn Wilson; Beng Kah Song; Muhammad Fahim; Sadequr Rahman (Biological Invasions, 2022)

Assessing the Accuracy of Farmers’ Nutrient Loss Risk Perceptions - Elizabeth R. Schwab; Margaret M. Kalcic; Robyn S. Wilson (Environmental Management, 2021)

Monitoring of heavy metal pollution in urban and rural environments across Pakistan using House crows (Corvus splendens) as bioindicator - Farheena Iqbal; Qasim Ayub; Robyn Wilson; Beng Kah Song; Amin Talei; Keng Yoon Yeong; Andreas Aditya Hermawan; Muhammad Fahim; Sadequr Rahman (Environmental Monitoring and Assessment, 2021)

The science and practice of ecological restoration: a mental models analysis of restoration practitioners - Emily H. Walpole; Eric Toman; Melanie Stidham; Robyn Wilson (Environment Systems and Decisions, 2020)

If you love it, let it go: the role of home attachment in wildfire evacuation decisions - Hugh D. Walpole; Robyn S. Wilson; Sarah M. McCaffrey (Environment Systems and Decisions, 2020)

Accounting for behavioral responses to environmental cues in complex systems - Robyn S. Wilson (Environment Systems and Decisions, 2018)

Expert judgment and uncertainty regarding the protection of imperiled species - Alexander Heeren; Gabriel Karns; Jeremy Bruskotter; Eric Toman; Robyn Wilson; Harmony Szarek (Conservation Biology, 2017)
Decisions concerning the appropriate listing status of species under the U.S. Endangered Species Act (ESA) can be controversial even among conservationists. These decisions may determine whether a species persists in the near term and have long‐lasting social and political ramifications. Given the ESA's mandate that such decisions be based on the best available science, it is important to examine what factors contribute to experts’ judgments concerning the listing of species. We examined how a variety of factors (such as risk perception, value orientations, and norms) influenced experts’ judgments concerning the appropriate listing status of the grizzly bear (Ursus arctos horribilis) population in the Greater Yellowstone Ecosystem. Experts were invited to complete an online survey examining their perceptions of the threats grizzly bears face and their listing recommendation. Although experts’ assessments of the threats to this species were strongly correlated with their recommendations for listing status, this relationship did not exist when other cognitive factors were included in the model. Specifically, values related to human use of wildlife and norms (i.e., a respondent's expectation of peers’ assessments) were most influential in listing status recommendations. These results suggest that experts’ decisions about listing, like all human decisions, are subject to the use of heuristics (i.e., decision shortcuts). An understanding of how heuristics and related biases affect decisions under uncertainty can help inform decision making about threatened and endangered species and may be useful in designing effective processes for protection of imperiled species.

Genetic diversity of native and introduced populations of the invasive house crow (Corvus splendens) in Asia and Africa - Urszula Krzemińska; Robyn Wilson; Beng Kah Song; Sampath Seneviratne; Sharif Akhteruzzaman; Joanna Gruszczyńska; Wiesław Świderek; Teh Ser Huy; Christopher M. Austin; Sadequr Rahman (Biological Invasions, 2016)

Human adaptations in food, energy, and water systems - Elena Irwin; Joseph Campbell; Robyn Wilson; Alessandra Faggian; Richard Moore; Nicholas Irwin (Journal of Environmental Studies and Sciences, 2016)

A typology of time‐scale mismatches and behavioral interventions to diagnose and solve conservation problems - Robyn S. Wilson; David J. Hardisty; Rebecca S. Epanchin‐Niell; Michael C. Runge; Kathryn L. Cottingham; Dean L. Urban; Lynn A. Maguire; Alan Hastings; Peter J. Mumby; Debra P.C. Peters (Conservation Biology, 2016)
Ecological systems often operate on time scales significantly longer or shorter than the time scales typical of human decision making, which causes substantial difficulty for conservation and management in socioecological systems. For example, invasive species may move faster than humans can diagnose problems and initiate solutions, and climate systems may exhibit long‐term inertia and short‐term fluctuations that obscure learning about the efficacy of management efforts in many ecological systems. We adopted a management‐decision framework that distinguishes decision makers within public institutions from individual actors within the social system, calls attention to the ways socioecological systems respond to decision makers’ actions, and notes institutional learning that accrues from observing these responses. We used this framework, along with insights from bedeviling conservation problems, to create a typology that identifies problematic time‐scale mismatches occurring between individual decision makers in public institutions and between individual actors in the social or ecological system. We also considered solutions that involve modifying human perception and behavior at the individual level as a means of resolving these problematic mismatches. The potential solutions are derived from the behavioral economics and psychology literature on temporal challenges in decision making, such as the human tendency to discount future outcomes at irrationally high rates. These solutions range from framing environmental decisions to enhance the salience of long‐term consequences, to using structured decision processes that make time scales of actions and consequences more explicit, to structural solutions aimed at altering the consequences of short‐sighted behavior to make it less appealing. Additional application of these tools and long‐term evaluation measures that assess not just behavioral changes but also associated changes in ecological systems are needed.

Factors influencing the distribution of the invasive house crow (Corvus splendens) in rural and urban landscapes - Robyn Fay Wilson; Dillon Sarim; Sadequr Rahman (Urban Ecosystems, 2015)

Climate change and human health—what influences the adoption of adaptation programming in the United States public health system? - Sana S. Syal; Robyn S. Wilson; J. Mac Crawford; Jonathan Lutz (Mitigation and Adaptation Strategies for Global Change, 2011)

Winter body temperature patterns in free-ranging Cape ground squirrel, Xerus inauris: no evidence for torpor - Wendy A. Wilson; M. Justin O’Riain; Robyn S. Hetem; Andrea Fuller; Linda G. Fick (Journal of Comparative Physiology B, 2010)

Comparison of genetic and cytogenetic maps of hexaploid wheat (Triticum aestivum L.) using SSR and DArT markers - Michael G. Francki; Esther Walker; Allison C. Crawford; Sue Broughton; Herbert W. Ohm; Iain Barclay; Robin E. Wilson; Robyn McLean (Molecular Genetics and Genomics, 2009)

Balancing Emotion and Cognition: a Case for Decision Aiding in Conservation Efforts - ROBYN S. WILSON (Conservation Biology, 2008)
Despite advances in the quality of participatory decision making for conservation, many current efforts still suffer from an inability to bridge the gap between science and policy. Judgment and decision‐making research suggests this gap may result from a person's reliance on affect‐based shortcuts in complex decision contexts. I examined the results from 3 experiments that demonstrate how affect (i.e., the instantaneous reaction one has to a stimulus) influences individual judgments in these contexts and identified techniques from the decision‐aiding literature that help encourage a balance between affect‐based emotion and cognition in complex decision processes. In the first study, subjects displayed a lack of focus on their stated conservation objectives and made decisions that reflected their initial affective impressions. Value‐focused approaches may help individuals incorporate all the decision‐relevant objectives by making the technical and value‐based objectives more salient. In the second study, subjects displayed a lack of focus on statistical risk and again made affect‐based decisions. Trade‐off techniques may help individuals incorporate relevant technical data, even when it conflicts with their initial affective impressions or other value‐based objectives. In the third study, subjects displayed a lack of trust in decision‐making authorities when the decision involved a negatively affect‐rich outcome (i.e., a loss). Identifying shared salient values and increasing procedural fairness may help build social trust in both decision‐making authorities and the decision process.